2015
DOI: 10.1021/cr500131f
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymer Nanogels for Drug/Nucleic Acid Delivery

Abstract: Figure 11. Schematic illustration of pullulan conjugated with deoxycholic acid (DOCA) (PUL-DOCA), and PUL-DOCA grafted with N α -Boc-Lhistidine (bHis) (PUL-DOCA-bHis); TEM images of PUL-DOCA-bHis NGs at pH 8.5 (a) and 6.2 (b). Adapted with permission from ref 148.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
346
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 409 publications
(348 citation statements)
references
References 368 publications
(816 reference statements)
1
346
0
1
Order By: Relevance
“…The erosion rate of alginate gels can be effectively tuned by the use of redox responsive crosslinking agents (Bawa, Pillay, Choonara, & du Toit, 2009;Li, Maciel, Rodrigues, Shi, & Tomas, 2015). It was shown that chemically crosslinked alginate hydrogels are sensitive for the reduction of the linking disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The erosion rate of alginate gels can be effectively tuned by the use of redox responsive crosslinking agents (Bawa, Pillay, Choonara, & du Toit, 2009;Li, Maciel, Rodrigues, Shi, & Tomas, 2015). It was shown that chemically crosslinked alginate hydrogels are sensitive for the reduction of the linking disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that chemically crosslinked alginate hydrogels are sensitive for the reduction of the linking disulfide bonds. The degradation of the hydrogel is triggered by a reductive environment, which induces the release of the incorporated active agent (Li et al, 2015;Maciel et al, 2013). Another promising strategy to produce redox responsive hydrogels is to crosslink alginate chains by a redox active metal ion which radically changes its affinity towards alginate when its oxidation state changes.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, rapid development of biodegradable polymeric carriers has attracted considerable attention, because of their versatile functional construction and biocompatibility for wide applications in biomedicine, such as drug delivery, gene delivery, tissue engineering, diagnosis, antibacterial/antifouling properties, and medical devices. [1][2][3][4][5][6][7][8][9] With regard to security, with rational design, biodegradable polymeric carriers are able to degrade into friendly biological catabolites, which is particularly important to reduce systemic cytotoxicity caused by the carrier. On the other hand, simplex biodegradable carriers cannot always meet rigorous demands, owing to the extremely hostile and complex environments in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…recognition factors) are immobilized onto their surface [5,6]. Well-known approaches for preparing nanogels include photolithographic and micromolding techniques, microfluidics, free radical heterogeneous polymerization in dispersion, nanoprecipitation and emulsion techniques [2,[7][8][9]. Water-in-oil (inverse) emulsion technique is the most widely used since it does not require any complicated equipment and the size of the resultant nanogels can be easily controlled.…”
Section: Introductionmentioning
confidence: 99%
“…intermolecular disulfide formation by the oxidation of thiol-groups [10]). Several examples are summarized in recent reviews of Matyjaszewski [2], Li [8] and Landfester [11] for the preparation of nanogels in the size range of 100-500 nm by inverse emulsion technique. Recently nanogels have been prepared mostly from natural polymers, e.g.…”
Section: Introductionmentioning
confidence: 99%